Analyzing Supply Chain Risks in the Tea Industry Using SCOR and HOR - Shalihin, Ahmad; D Sihombing, Clarisa; Sinulingga, Sukaria (DINAMIS, 2025)
The tea plantation sector has a complex supply chain, and the production process at the black tea processing company is often affected by various operational issues. One of the main problems is delays in raw material processing caused by the late arrival of wet tea leaves, which are further aggravated by machine breakdowns and a lack of worker discipline. These conditions can disrupt or even halt production, emphasizing the need for effective risk mitigation measures. This study aims to identify risk factors in the black tea production supply chain using the Supply Chain Operations Reference (SCOR) model and to formulate priority mitigation strategies through the House of Risk (HOR) method. The results of the HOR Phase I analysis identified 21 risk events and 4 priority risk agents with a cumulative Aggregate Risk Potential (ARP) value of 76.82%. The four main risk agents are: (A2) irregularities or delays in the transportation of wet tea leaves, (A6) lack of worker discipline, (A7) machine damage or malfunction, and (A8) low employee awareness during work. The HOR Phase II analysis produced seven mitigation actions, which were ranked based on the Effectiveness to Difficulty Ratio (ETD). The top three priority actions are (PA₁) conducting analysis and evaluation of employee performance (ETD = 6.00), (PA₃) increasing supervision of foremen at each station (ETD = 5.00), and (PA₂) creating a schedule for picking wet tea leaves (ETD = 5.00). Supporting actions include quality control of raw materials (PA₄), routine machine maintenance (PA₅), increasing awareness to work carefully (PA₇), and limiting machine loads to maximum capacity (PA₆). The results indicate that human and managerial factors—including employee performance, supervision, and work scheduling—are the dominant contributors to supply chain risk. Therefore, mitigation strategies should prioritize management and behavioral improvements, supported by technical maintenance and process control, to enhance the efficiency, reliability, and resilience of the black tea supply chain.